A case report of heterozygous TINF2 gene mutation associated with pulmonary fibrosis in a patient with dyskeratosis congenita. Issue 19 (May 2018) - Du, Hongchun; Guo, Yubiao; Ma, Di; Tang, Kejing; Cai, Decheng; Luo, Yifeng; Xie, Canmao
Abstract: Rationale: Dyskeratosis congenita (DC) is a rare inherited disease characterized by the classical mucocutaneous triad. Pulmonary fibrosis, bone marrow failure, and solid tumors are the main causes of mortality in DC. Pathogenic variants in TERT, TERC, and DKC1 have been identified in individuals with familial pulmonary fibrosis. Mutations in TINF2 gene have been reported to be associated with bone marrow failure in most cases. However, the relationship between TINF2 mutation and pulmonary fibrosis is not yet clear. Patient concerns: Here, we report the case of a 32-year-old woman presented with irritating cough for 2 years and progressive breathlessness for 6 months. Diagnoses: The patient was diagnosed with DC based on the following clinical evidences. Along with some family members, she had the typical mucocutaneous triad and pulmonary fibrosis. A heterozygous mutation (c.844C>T), located in exon 6 of TINF2 gene, that changed arginine to cysteine (Arg282Cys) was identified in this proband by whole exome sequencing. Interventions: The patient received corticosteroid therapy but refused to receive lung transplantation. Outcomes: The proband died of respiratory failure 4 months after the diagnosis. The missense mutation was located in the conserved region of TINF2 gene and predicted to be deleterious by altering the protein structure. Lessons: Lung transplantation should be considered for improved survival of patients with DC, and pulmonary fibrosis. Whole exome and whole genome sequencing should be widely used in the identification of such rare genetic variants for clinical diagnosis. The study of DC with pulmonary fibrosis can provide a more appropriate means of clinical research and therapy to the unfortunate patients who suffer from this rare disorder.